(3GdNVhY GdGNJjGQj cVGHW ddGNJUGU GdbVGFj GdOhdj ddeMGce GdeUQjI (B/s - (3SdGe, CMeO QTGO eMehOs ((3GdgQe (B[(3eUQ(B] :s (3OGQ CHh GdeLO,s, 2019)
(3jJfGhd cJGH (B((3GdNVhY GdGNJjGQj cVGHW ddGNJUGU GdbVGFj GdOhdj ddeMGce GdeUQjI(B) (3hGdPj bGe HJCdjag O(B. (3CMeO QTGO SdGe aj MhGdj (B(173) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdNVhY GdGNJjGQj(B)(3, eSJYQVG eMJhjGJ GdcJGH aj GdehVhYGJ GdJGdjI (B: (3eHMK JegjOj (B: (3GdGNJUGU GdbVGFj GdOhdj ddeMGce GdeUQjI, GdaUd GdChd (B: (3GdNVhY GdGNJjGQj Hjf GdGNJUGUjf GdOGNdj hGdOhdj hGdBKGQ GdeJQJHI Ydjg, GdaUd GdKGfj (B: (3GdbGfhf GdhGLH GdJWHjb Ydi VGHW GdNVhY GdGNJjGQj, GdaUd GdKGdK (B: (3GdaQb Hjf GdNVhY GdGNJjGQj heG bO jJTGHg, NGJeI hJhUjGJ, bGFeI GdeQGLY(B. s
(3HHdjhLQGajI (B: (3UaMI (B161-166.s
Keywords: (3GdeMGces -- (3eUQs; (3JfajP GdCMcGes -- (3eUQs; (3GdGNJUGU GdbVGFj (B((3bGfhf Ohdj(B)s